ЗАҢНАМАДА ТЕРМИННІҢ АТҚАРАТЫН РӨЛІ - Esenkul, Сафуани; Aliy, Кадирова (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2015)
To the article examples are driven, where different application of words of terms inflicts a damage to execution of laws and authors prove that their uniform application must be an inalienable rule in a законотворческом process.